Implementation and Evaluation of Preimplantation Genetic Testing at Vilnius University Hospital Santaros Klinikos - Stukaitė-Ruibienė, Eglė; Gudlevičienė, Živilė; Amšiejienė, Andrė; Dagytė, Evelina; Gricius, Rimantas; Grigalionienė, Kristina; Utkus, Algirdas; Ramašauskaitė, Diana (Acta medica Lituanica, 2022)
Background and Objectives: The most effective treatment of infertility is in vitro fertilization (IVF). IVF with Preimplantation Genetic Testing (PGT) allows to identify embryos with a genetic abnormality associated with a specific medical disorder and to select the most optimal embryos for the transfer. PGT is divided into structural rearrangement testing (PGT-SR), monogenetic disorder testing (PGT-M), and aneuploidy testing (PGT-A). This study mostly analyzes PGT-SR, also describes a few cases of PGT-M. The aim of this study was to implement PGT procedure at Vilnius University Hospital Santaros Klinikos (VUHSK) Santaros Fertility Centre (SFC) and to perform retrospective analysis of PGT procedures after the implementation. Materials and Methods: A single-center retrospective analysis was carried out. The study population included infertile couples who underwent PGT at SFC, VUHSK from January 01st, 2017 to December 31st, 2020. Ion PGM platform (Life Technologies, USA) and Ion ReproSeq PGS View Kit (Life Technologies, USA) were used for the whole genome amplification. Results were assessed using descriptive statistics. Results: PGT was successfully implemented in VUHSK in 2017. During the analyzed time period, thirty-four PGT procedures were performed for 26 couples. Two procedures were performed in 2017, 7 procedures – in 2018, 13 – in 2019, and 12 – in 2020. In comparison with all IVF procedures, 2.5% procedures were IVF with PGT, a highest percentage was in 2020 (3.8% of all procedures). The main indication for PGT was balanced chromosomal rearrangements (in 85.3% cases). In all 34 cases 515 oocytes were aspirated in total, 309 oocytes were fertilized, oocytes fertilization rate exceeded 60%. A normal diploid karyotype was found in 46 (16.8%) biopsied embryos. Out of all PGT procedures, 9 (26.5%) resulted in a clinical pregnancy. Six (66.7%) pregnancies were confirmed in 2019, and 3 (33.3%) – in 2020. Three (33.3%) pregnancies resulted in spontaneous abortion, 6 (66.7%) – in delivery. Conclusions: The implementation of PGT in VUHSK was successful. The most common indication for PGT was a reciprocal translocation. Oocytes fertilization rate exceeded 60%, a normal karyotype was found less than in one-fifth of biopsied embryos. A highest clinical pregnancy rate was achieved in 2019 when almost half of women conceived, which is probably related to the experience gained by the multidisciplinary team. This is the first study analyzing IVF with PGT in Lithuania, however, the results should be interpreted with caution due to a low number of total procedures performed.